1998
DOI: 10.1016/s0002-9270(98)00172-5
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and celiac disease: clinical, serological, and echographic study

Abstract: An elevated prevalence of clinical and subclinical autoimmune thyroid autoimmunity was found in Sardinian celiac patients, especially in those displaying the DQB1*0502 genotype; this finding could be related to a particular genetic background of the Sardinian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Most of the patients with CD were suffering from HT, but there was no significant statistical relation between CD and HT; however, in Hadithi et al study, there is relation between HT and CD [5], summarized prevalence of CD in hypothyroid patients in some studies (Table 3) [1218]. Conversely, there is also an increased prevalence of immune-based disorders among patients with CD (Table 4) [5, 79, 1921]. Female sex predominance was seen patients with celiac, but it was not significant ( P = 0.626), however other reports show female sex predominance role in this disease [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients with CD were suffering from HT, but there was no significant statistical relation between CD and HT; however, in Hadithi et al study, there is relation between HT and CD [5], summarized prevalence of CD in hypothyroid patients in some studies (Table 3) [1218]. Conversely, there is also an increased prevalence of immune-based disorders among patients with CD (Table 4) [5, 79, 1921]. Female sex predominance was seen patients with celiac, but it was not significant ( P = 0.626), however other reports show female sex predominance role in this disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hashimotos thyroiditis (HT) is defined by the presence of high serum thyroid antibody concentrations (TG and/or TPO) [5]. Likewise, several studies reported prevalence's ranging from 10% to 30% [69] for autoimmune thyroid disease, and from 4 to 19% for HT in patients with CD [710]. Screening patients with autoimmune thyroid disease for CD and vice versa can give an accurate perception to this association [1].…”
Section: Introductionmentioning
confidence: 99%
“…As in the former studies that investigated DH patients, we also found increased values of thyroid antibodies and a higher prevalence of thyroid disease in females than in males. To our knowledge there is only one recently published paper evaluating thyroid disorders in coeliac patients by sonography [16]. Prospective studies investigating thyroid disorders in patients with coeliac disease are rare.…”
Section: Discussionmentioning
confidence: 99%
“…3 Also, it is known that, in celiac disease, there is an increased frequency of endocrinological diseases of autoimmune etiology. Among these, in patients with autoimmune thyroiditis (Hashimoto’s thyroiditis, Graves’ disease), type I diabetes mellitus and Addison’s disease, the frequency of celiac disease is much higher than in the normal population 48. It is known that the above-mentioned association is important in terms of disease treatment.…”
Section: Introductionmentioning
confidence: 99%